Reading Unruly : Interpretation and Its Ethical Demands - Zalloua, Zahi Anbra, 1971- (Book collections on Project MUSE., 2014)
"Drawing on literary theory and canonical French literature, Reading Unruly examines unruliness as both an aesthetic category and a mode of reading conceived as ethical response. Zahi Zalloua argues that when faced with an unruly work of art, readers confront an ethical double bind, hesitating then between the two conflicting injunctions of either thematizing (making sense) of the literary work, or attending to its aesthetic alterity or unreadability. Creatively hesitating between incommensurable demands (to interpret but not to translate back into familiar terms), ethical readers are invited to cultivate an appreciation for the unruly, to curb the desire for hermeneutic mastery without simultaneously renouncing meaning or the interpretive endeavor as such. Examining French texts from Montaigne's sixteenth-century Essays to Diderot's fictional dialogue Rameau's Nephew and Baudelaire's prose poems The Spleen of Paris, to the more recent works of Jean-Paul Sartre's Nausea, Alain Robbe-Grillet's Jealousy, and Marguerite Duras's The Ravishing of Lol Stein, Reading Unruly demonstrates that in such an approach to literature and theory, reading itself becomes a desire for more, an ethical and aesthetic desire to prolong rather than to arrest the act of interpretation."--